GLOBAL FINANCIAL CRISIS AND RESTRUCTURING OF GLOBAL ECONOMY – EVIDENCE FROM GLOBAL FDI INFLOWS, OUTFLOWS AND NETFLOWS - Navitha Thimmaiah (European Scientific Journal, ESJ, 2013)
The present paper is an attempt to analyze the impact of recent global slow down on the restructuring of the global economy. It tries to provide empirical basis for the same through examining important international macroeconomic variables like FDI Inflows, FDI Outflows, FDI Net flows etc. Regression, Correlation and Granger Causality tests have been employed for recognizing trends and relationships. The results indicate that the developing region of the world is improving their economic status in international arena in terms of GDP growth rates, FDI inflows and outflows.